Phasing-out of legacy brominated flame retardants: The UNEP Stockholm Convention and other legislative action worldwide. (November 2020) - Sharkey, Martin; Harrad, Stuart; Abou-Elwafa Abdallah, Mohamed; Drage, Daniel S.; Berresheim, Harald
Highlights: Concentration limits imposed on legacy-BFRs to prevent further commercial use. Notable variance in worldwide legislation regarding BFRs in consumer items & waste. Limited effectiveness of concentration limits due to replacement/novel BFR use. Lack of effective screening method may hinder plastic recycling processes. Future legislation must be proactive in preventing cycle of hazardous chemical use. Abstract: Due to their toxicity and persistence, several families of brominated flame retardants (BFRs) have been listed as persistent organic pollutants (POPs) in the Stockholm Convention, a multilateral treaty overseen by the United Nations Environment Programme. This treaty mandates that parties who have signed must take administrative and legislative actions to prevent the environmental impacts that POPs pose, both within their jurisdictions and in the global environment. The specific BFRs listed in the Stockholm Convention are Polybrominated Diphenyl Ethers (PBDEs), Hexabromocyclododecane (HBCDD), and Hexabromobiphenyl (HBB), chemicals which must therefore be heavily restricted within the jurisdictions of the signatories. As an example, within the EU, hexabromobiphenyl (HBB), the PBDE commercial mixtures, and HBCDD are almost entirely prohibited in terms of both production and use in commercial goods. Waste articles containing excess concentrations of these BFRs are similarly restricted and must be disposed of in a manner that destroys or irreversible transforms the BFR in question. In some cases, specific exemptions for these limits are defined by the Convention for certain parties: for example, Penta- and Octa-BDE can be present in waste materials for recycling until 2030, while Deca-BDE can be applied to some aviation and automotive applications until 2036. However, in such cases, very specific criteria and guidelines apply for their use and/or production. Worldwide, China, Japan, India, and the United States of America have made significant advances in the regulation of POPs, in line with the provisions of the Stockholm Convention. China has established concentration limits for Penta- and Octa-BDEs in electronic goods. It is also currently availing of an exemption to allow for the use of HBCDD and has not yet ratified the Convention with regards to Deca-BDE. Japan meanwhile has classified HBB and Penta-/Octa-BDE compounds as Class I Specified Chemical Substances which virtually prohibits the manufacture, import, and use of these chemicals in all applications. India has banned the manufacture, trade, import, and use of HBB, HBCDD and some PBDEs, and has established concentration limits for all PBDEs in certain electrical goods. Finally, the United States has no federal mandate for the restriction of POPs and has not ratified the annexes to the Convention requiring them to do so. However, thirteen states have implemented their own state-wide concentration limits on a variety of flame retarding chemicals in various commercial applications. Though these limits worldwide are a very positive step for the removal of POP-BFRs from the environment, the increased use of replacement flame retardants renders such legislation only partially effective. The lack of effective screening mechanisms in waste management facilities means that BFR-treated plastics can be inadvertently recycled and remain in circulation. The rise in the use of novel BFRs (NBFRs) can furthermore hinder screening methods currently being developed and the additives themselves may pose similar issues to their predecessors owing to their similar chemical properties. Thus, restrictions on current BFRs will result in the use of new flame retardants, which may in turn be banned and replaced once again. Further research into and development of methods to screen for hazardous chemicals in end of life materials is therefore of the utmost importance. This must be coupled with pro-active legislation that eliminates the need for using such persistent and potentially harmful chemicals in the future.